Aging and cognition : research methodologies and empirical advances - Bosworth, Hayden B.; Hertzog, C. K. (Christopher K.), 1952- (Decade of behavior., 2009)
"As the world's population ages, the study of aging and its effects on cognition becomes increasingly important. Aging and Cognition: Research Methodologies and Empirical Advances takes an interdisciplinary look at cognitive aginghow it happens and how to study it. The first part of the book explores methods for measuring cognitive change, including how to study cohort effects. How can we account for differences in cognitive performance from one cohort to another? Should we assume factor invariance across cohorts or time? These issues are treated in the context of new and existing empirical research, making the discussion of methodological issues more concrete and accessible. The second part of the book explores the social and psychological factors associated with cognitive aging. For example, to what extent do socioeconomic status, optimism, and personal sense of control affect aging? Is the controversial "use it or lose it" theory of cognition valid? Finally, the concluding section explores how to use research findings to improve the everyday functioning of adults-- a challenging task because everyday functioning relies on complex cognitive tasks and most cognitive research measures only basic cognitive tasks. The chapter in this final section uses medication adherence as an example of deriving real-world solutions from cognitive research results. With its emphasis on social and contextual factors that influence aging, this book showcases both substantive and methodological developments in the field. It will be useful to everyone who studies aging and cognition"--Jacket. (PsycINFO Database Record (c) 2009 APA, all rights reserved)